2018
DOI: 10.1007/s00128-018-2326-4
|View full text |Cite
|
Sign up to set email alerts
|

Total and Methyl Mercury Concentrations in Antarctic Toothfish (Dissostichus mawsoni): Health Risk Assessment

Abstract: The concentrations of total mercury (THg) in different organs of the Antarctic toothfish (Dissostichus mawsoni) collected from CCAMLR research blocks in Subarea 88.3 and Division 58.4.1 off the coast of Antarctica were determined. The results revealed THg concentrations of 0.165 ± 0.095 mg/kg (0.023-0.454 mg/kg, wet weight) in the Antarctic toothfish. In muscle, methyl mercury (MeHg) accounted for approximately 40% of the THg. In a comparison analysis, muscle and liver tended to bioaccumulate the highest level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Other studies conducted between these years are more consistent with earlier results, reporting mean mercury levels below 0.25 mg kg -1 in the southwest Pacific sector and elsewhere in the Southern Ocean (Son et al 2014, Yoon et al 2018. We calculated the size of fish using allometric equations, while previous studies used measurements of whole fish (Hanchet et al, 2012;Son et al, 2014;Yoon et al, 2018). This may have contributed to the lower mean size of fish in our study.…”
Section: Mercury In D Mawsoni Over the Last 2 Decades And Possible Environmental Implicationssupporting
confidence: 88%
See 3 more Smart Citations
“…Other studies conducted between these years are more consistent with earlier results, reporting mean mercury levels below 0.25 mg kg -1 in the southwest Pacific sector and elsewhere in the Southern Ocean (Son et al 2014, Yoon et al 2018. We calculated the size of fish using allometric equations, while previous studies used measurements of whole fish (Hanchet et al, 2012;Son et al, 2014;Yoon et al, 2018). This may have contributed to the lower mean size of fish in our study.…”
Section: Mercury In D Mawsoni Over the Last 2 Decades And Possible Environmental Implicationssupporting
confidence: 88%
“…The model was not improved by the inclusion of either depth (p≈ 1.00) or standard length (p≈ 0.67) (Annex 1). There was little difference between intercepts for different levels of the grouping variable, longline (variance = 0.0006), and the similar values for R 2 m and R 2 c confirm that the fixed effect variables explain almost all of the explained variability ( Mean mercury levels in D. mawsoni muscle recorded in the current study were higher than those reported in all previous studies (Hanchet et al, 2012;Son et al, 2014;Yoon et al, 2018). The highest single value in this study (1.94 mg kg -1 wwt) was almost 3 times higher than the previous maximum value [~0.70 mg kg -1 in D. mawsoni captured in 2006 (Hanchet et al, 2012)].…”
Section: Relationship Between Mercury Concentrations In D Mawsoni and Biological And Habitat Variablessupporting
confidence: 79%
See 2 more Smart Citations
“…The main comprehensive source of information on Hg bioaccumulation in Southern Ocean squid is the recent work by Seco et al (2020), which documents the concentrations of total, and proportions of organic, mercury in the tissues of 8 squid species caught around South Georgia between 2007 and 2017. While several studies have shown that Patagonian toothfish D. eleginoides have elevated mercury levels (Méndez et al, 2001;McArthur et al, 2003;Guynn and Peterson, 2008), Hanchet et al (2012), Son et al (2014), andYoon et al (2018) reported lower levels of mercury concentrations for the Antarctic toothfish D. mawsoni, usually not exceeding the 0.5 mg kg −1 food safety threshold.…”
Section: Pollutionmentioning
confidence: 96%